2011
DOI: 10.1149/1.3519870
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Electric Fields to Aerosol Assisted Chemical Vapor Deposition Reactions

Abstract: Chemical vapor deposition methodologies are widely employed in a variety of fields such as microelectronics and glazing. Control of film growth and microstructure, and hence film properties, may be limited by precursor properties such as volatility or decomposition chemistry. In this paper we report how the incorporation of an applied electric field to aerosol assisted chemical vapor deposition reactions of vanadyl acetylacetonate in alcohols can influence the microstructure and growth of thin films of vanadiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 35 publications
1
27
0
Order By: Relevance
“…Previous investigations [10][11][12][13] have shown that the application of an electric field during a CVD reaction influences the crystallographic orientation, microstructure and subsequent properties of the deposited materials. Indeed it is well known that sensor microstructure plays an important role in determining the gas response of a gas sensing material [24].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous investigations [10][11][12][13] have shown that the application of an electric field during a CVD reaction influences the crystallographic orientation, microstructure and subsequent properties of the deposited materials. Indeed it is well known that sensor microstructure plays an important role in determining the gas response of a gas sensing material [24].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed it is well known that sensor microstructure plays an important role in determining the gas response of a gas sensing material [24]. We have suggested previously that a variety of phenomena may be occurring when an electric field is applied to CVD growth [10][11][12][13]. Applied electric fields can cause an increase in growth rate and nucleation rate leading to pseudo dendritic type morphologies as a result of accelerating gas phase species towards the surface [10].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations